Hubungan Kinerja Petugas Kesehatan Dengan Kejadian Missfile Dokumen Rekam Medis - Tarigan, Sylva Flora Ninta; Hadisi, Jahra; Ahmad, Zul Fikar (Madu : Jurnal Kesehatan, 2023)
Health workers play an important role in the service flow of medical record documents. Therefore, officers must have good performance so as not to experience problems in the service flow of medical record documents. The purpose of this study was to analyze the relationship between the performance of health workers and the incidence of missfile medical record documents. The type of research is analytic observational with cross sectional study design. The population was all health workers totaling 35 people and the sample in this study was 30 people in the work area of the Tilango Health Center, Gorontalo Regency. The sampling technique used purposive sampling. Data were collected using a questionnaire and then analyzed using the chi-square test. The results showed that of performance of health workers mostly in the good category 63.3% and did not missfile medical record documents 53.3%. There is a relationship between the performance of health workers and the incidence of missfile medical record documents (p value = 0.029). It is recommended that the health center further improve and maintain the performance of health workers, especially in carrying out their duties as medical record officers in order to maintain and store medical record documents properly.